2020
DOI: 10.18632/aging.103333
|View full text |Cite
|
Sign up to set email alerts
|

M6A-related bioinformatics analysis reveals that HNRNPC facilitates progression of OSCC via EMT

Abstract: Increasing evidence suggests that N6-methyladenosine (m6A) has a vital role in cancer progression. Therefore, we aimed to explore the prognostic relevance of m6A-related genes in oral squamous cell carcinoma (OSCC). First, Expression profiles were downloaded from The Cancer Genome Atlas (TCGA) and m6A-related genes were extracted afterwards. Then, cluster analysis and principal component analysis (PCA) were used to analyze m6Arelated genes. And differentially-expressed analysis was performed in R software. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 27 publications
3
53
0
Order By: Relevance
“…Only recently the expression profiles of 13 m6A-related genes in 317 OSCC and 32 normal samples from The Cancer Genome Atlas (TCGA) database had been analyzed and found a significantly higher expression of eight genes, including METTL3 and METTL14, in tumor tissues. Furthermore, an increase of m6A levels in total tumor RNA could be detected using an antibody-based quantification kit [ 175 ]. The upregulation of METTL3 in oral cancer was also seen in two additional studies that also report a correlation of METTL3 expression with poor prognosis of OSCC patients [ 176 , 177 ].…”
Section: Rbps Associated With Migration Invasion and Metastasis mentioning
confidence: 99%
“…Only recently the expression profiles of 13 m6A-related genes in 317 OSCC and 32 normal samples from The Cancer Genome Atlas (TCGA) database had been analyzed and found a significantly higher expression of eight genes, including METTL3 and METTL14, in tumor tissues. Furthermore, an increase of m6A levels in total tumor RNA could be detected using an antibody-based quantification kit [ 175 ]. The upregulation of METTL3 in oral cancer was also seen in two additional studies that also report a correlation of METTL3 expression with poor prognosis of OSCC patients [ 176 , 177 ].…”
Section: Rbps Associated With Migration Invasion and Metastasis mentioning
confidence: 99%
“…In recent years, EMT has been believed to be a key step in the invasion and metastasis of cancer cells [ 39 ]. Previous studies have shown that several hnRNP family members are implicated in the regulation of EMT in several human cancer types and are regarded as cancer metastasis suppressors [ 17 , 18 , 20 , 40 , 41 ]. We investigated the function of HNRNPU in regulating EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, HNRNPC can regulate the stability and translation levels of bound mRNA molecules [ 38 ], while M6A can promote the binding of mRNAs and HNRNPC through the "m6A-switch" mechanism, thus regulating mRNA splicing and affecting the expression of the corresponding proteins [ 39 ]. Huang et al found that HNRNPC can promote cell proliferation, migration, and invasion [ 40 ], which was closely related to the occurrence and progression of cancer and was an important M6A regulatory factor that caused poor prognosis of patients. YTHDF1 can recognize and bind the M6A methylation of mRNA, thus inhibiting the translation of mRNA.…”
Section: Discussionmentioning
confidence: 99%